A 10% blood pressure drop from baseline during mechanical thrombectomy for stroke is strongly associated with worse neurological outcomes. (26th September 2019) - Valent, Arnaud; Sajadhoussen, Amard; Maier, Benjamin; Lapergue, Bertrand; Labeyrie, Marc-Antoine; Reiner, Peggy; Consoli, Arturo; Fischler, Marc; Gayat, Etienne; Leguen, Morgan
Abstract : Background: Mechanical thrombectomy (MT) for acute ischemic stroke can be performed under local anesthesia, with or without conscious sedation (CS), or under general anesthesia (GA). The hemodynamic consequence of anesthetic drugs may explain why GA may be associated with worse outcomes. We evaluated the association between hypotension duration during MT and the 90 day functional outcome under both anesthetic regimens. Methods: Patients were included in this retrospective study if they had an ischemic stroke treated by MT under GA or CS. The main exposure variable was the time below 90% of the reference value of arterial pressure measured before MT. The primary outcome was poor functional outcome defined as a 90 day modified Rankin Score ≥3. Results: 371 patients were included in the study. GA was performed in 42%. A linear association between the duration of arterial hypotension and outcome was observed. The odds ratio for poor functional outcome of 10 min under 90% of the baseline mean arterial pressure was 1.13 (95% CI 1.06 to 1.21) without adjustment and 1.11 (95% CI 1.02 to 1.21) after adjustment for confounding factors. The functional outcome was poorer for patients treated under GA compared with CS, but the association with the depth of hypotension remained similar under both conditions. Conclusion: In this study, we observed a linear association between the duration of hypotension during MT and the functional outcome at 90 days. An aggressive and personalized strategy for the treatment of hypotension should be considered. Further trials should be conducted to address this question.